OPTIMIZING MEDIA STERILIZATION VIA CHLORINE DIOXIDE AND AUTOCLAVING OF PAULOWNI MICROPROPAGATION - M. T. Al-Jubori,; F. M. K. AL-Dabbagh,; E. W. Al-Ani, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
This study was aimed to investigat integrated system for in vitro growth of paulownia plants by assessing the efficacy of chlorine dioxide (ClO2) as an alternative to autoclave in sterilizing culture medium. Therefore, this study was devised to compare autoclave sterilization at three different times (5, 10, and 15) minutes and three different concentrations of ClO2 (0, 0.4, 0,8, 1) mg/L. The results showed that, compared with (0.4) mg/L concentration,  concentrations of (0.8 and 1) mg/L are more effective at sterilizing the culture medium. ClO2 sterilization improved individual single node growth more than autoclave sterilization. Since ClO2 is non-toxic, it could be used as a safe alternative to autoclave when propagating paulownia in vitro. Culture medium sterilization in the autoclave takes only 5 minutes, compared with the standard 15 minutes. At initiation stage, growing single nodes in the Murashige and Skoog medium (MS)  prepared with 0.5 mg/L Benzyl  Adenine (BA) resulted in a 100% response rate, while doing the same in the Woody Plant Medium (WPM)  resulted in a 20% response rate. The 1 BA + 0 a-Naphthalene Acetic Acid    ( NAA) mg/L treatment was effective during vegetative multiplication stage, the highest average number of shoots produced by a plant treated with  the mentioned concentration was   6.40 shoot per explant. During the rooting stage, Indole Butyric Acid (IBA) at a concentration of 2 mg/L was more effective than NAA, the typical number of roots produced by with 27.40 root per shoot. After two months in their natural environment, the plants' acclimatization rate was at a perfect 100%.